La aplicación de los derechos de protección en la sustanciación del proceso ejecutivo. - Cuenca Guachizaca, Víctor Manuel (2011)
The Constitution of the Republic of Ecuador, provides for all Ecuadorians, so-called protection rights, among which are guarantees and effective judicial protection, the right to defense, and the right to legal security. The validity of the above rights is crucial to ensure compliance with the guarantees that have people involved in a legal process, as parties to the proceedings, rights holders. However, when reviewing the Ecuadorian Civil Procedure Code can be determined that the legal proceedings mentioned body by regulating regard to executive action, states that the performer has the right to pursue all remedies that are applicable within the regular process, while the debtor is the victim of the executive process may only appeal the sentence, without being able to turn to other avenues of appeal in defense of their rights. Civil procedural law in question, is unconstitutional, since it directly violates the guarantees to which reference has been made before, and is at risk of violation the interests and rights in the equity area will attend in person to be executed the execution process. The problems mentioned in the above lines, is addressed in this research project which has been well supported by theoretical, conceptual, legal and doctrinal, with results obtained through field research process, based on which conclusions are drawn and recommendations, and finally makes the approach of a proposed amendment to theCivil Procedure Code, in order to guarantee for the person executed the implementation of all rights and guarantees as a party to the proceedings, we recognize the Constitution of the Republic of Ecuador.